2009
DOI: 10.1021/nl9013666
|View full text |Cite
|
Sign up to set email alerts
|

Multi Tbit/in2 Storage Densities with Thermomechanical Probes

Abstract: Exploiting the spatial resolution of scanning probes presents an attractive approach for novel data storage technologies in particular for large-scale data repositories because of their inherent potential for high storage density. We show that multi-Tbit/in(2) density can be achieved by means of thermomechanically embossing the information as indentation marks into a polymer film. The data density is determined by the nonlinear interaction between closely spaced indents and the fundamental scaling relations go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…Later, a storage capacity of 840 Gb/in using eight probes operating in parallel was demonstrated [14]. Furthermore, a feasibility study has shown that densities of 4 Tb/in can be achieved by using an advanced polymer medium [216]. At the time of this writing, this is the only probe-storage technology that has reached this level of functionality.…”
Section: B Storage Mediummentioning
confidence: 96%
“…Later, a storage capacity of 840 Gb/in using eight probes operating in parallel was demonstrated [14]. Furthermore, a feasibility study has shown that densities of 4 Tb/in can be achieved by using an advanced polymer medium [216]. At the time of this writing, this is the only probe-storage technology that has reached this level of functionality.…”
Section: B Storage Mediummentioning
confidence: 96%
“…Experimental results using single cantilevers have shown that data can be recorded at a density of 641 Gb/in and read back with raw error rates better than 10 [20]. Furthermore, a feasibility study has shown that densities of 4 Tb/in can be achieved using an advanced polymer medium [21].…”
Section: Data Allocation In Afm-based Probe Storage Devicesmentioning
confidence: 99%
“…Extremely high densities, up to and beyond 4 Tbit/sq.in. have recently been successfully written and read by IBM using this thermo-mechanical write/read technique [11]. The IBM researchers noted that the rim that forms around each written pit is the most critical parameter governing how closely indents can be written, and therefore plays a key role in achievable density.…”
Section: Introductionmentioning
confidence: 99%